1389Do associations between a healthy lifestyle and incidence of cancer differ by genetic risk?. (2nd September 2021) - Byrne, Stephanie; Boyle, Terry; Benyamin, Beben; Lee, Sang Hong; Ahmed, Muktar; Hypponen, Elina
Abstract: Background: It is unknown whether relationships between lifestyle and cancer differ by genetic risk. We investigated this for 13 cancer types using prospective data from the UK Biobank. Methods: In 2006-2010, participants aged 37-73 years completed an assessment and provided biological samples. Those of European ancestry with no history of malignant cancer were included in our analysis (n = 196, 485). For each individual, a healthy lifestyle index (HLI) was calculated based on recommendations, and polygenic risk scores (PRSs) were computed for 13 cancer types. Relationships with cancer incidence were assessed by cox regression, adjusting for age, sex, assessment centre, birth location, and measures of socioeconomic status. Interactions between the HLI and PRSs were explored. Results: For all cancer outcomes, a high genetic risk was associated with an increased cancer risk, or there was a trend in that direction. Those in the top PRS tertile had a greater than 2-fold increased risk of colorectal cancer (HR[95%CI]=2.18[1.90, 2.49]), pancreatic cancer (2.39[1.71, 3.32]) and lymphocytic leukemia (2.45[1.67, 3.59]). An unhealthy lifestyle was associated with a higher cancer risk for 8 cancer types, with strong relationships observed for lung (3.41[2.76, 4.20]), pancreatic (2.06[1.47, 2.91]), bladder (1.95[1.43, 2.66]) and kidney cancers (1.90[1.43, 2.54]). No interactions between HLI and PRSs were detected (all interaction p-values>0.10). Conclusions: Associations between lifestyle and cancer incidence did not differ by genetic risk. Key messages: A healthy lifestyle can reduce the risk of several cancers, even in those who are genetically predisposed to develop cancer.